Familial hypersensitivity pneumonitis triggered by Cladosporium herbarum exposure during carpooling. Issue 3 (17th August 2020) - Planté-Bordeneuve, Thomas; Gilbert, Olivier; Latinne, Dominique; Bruffaerts, Nicolas; Ghaye, Benoit; Froidure, Antoine
Hypersensitivity pneumonitis (HP) is a respiratory disease caused by an inappropriate immune response to environmental antigens affecting the small airways and lung parenchyma. With an incidence of 0.3–1.94 cases per 100 000 per year [1, 2], HP is the third cause of interstitial lung disease (ILD) [3]. Seven to 17% of patients with HP report a positive family history for ILD [4, 5], suggesting predisposing genetic factors. This series reports cases of Cladosporium herbarum- related HP due to an uncommon exposure source, illustrating the genetic background underlying HP, and highlighting the role of environmental home inquiry and serum precipitins in diagnosis and follow-up https://bit.ly/3hzvE4w